Flowering of the seagrass Posidonia oceanica in NW Mediterranean: is there a link with solar activity? - MONTEFALCONE, M.; GIOVANNETTI, E.; MORRI, C.; PEIRANO, A.; BIANCHI, C. N. (Mediterranean Marine Science, 2013)
Time series on the leaf biometry and rhizome production of the endemic Mediterranean seagrass Posidonia oceanica (L.) Delile were investigated in a meadow of the Ligurian Sea (NW Mediterranean) in order to assess changes in the plant growth during a massive flowering event occurred in 2003, in coincidence with the warmest summer temperatures recorded in the last centuries. P. oceanica exhibited the highest values of leaf surface area during the flowering year and the highest values of rhizome production in the previous year. The years immediately following the flowering event were characterized by a decrease in both parameters. Comparison of the years of massive flowering events reported in the literature at the whole Mediterranean-wide spatial scale with the historical series (spanning the last 50 years) of the air temperature and of the sunspot number suggested that intense solar activity, and not warmer temperature per se, was likely to be the main trigger of massive flowering events in Posidonia oceanica.